Arabic Language Representation in Naming Children: A Case of Shift Naming of Melayu Children - Novi Ulfa Safitri; Moh. Fery Fauzi (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
The phenomenon of the shift in the naming of Melayu children, which used to use naming from the Arabic language, has recently shifted in Palembang, South Sumatera, Indonesia. It has an effect on how parents perceive the Arabic language. This study aimed to 1) analyze the trend of naming Melayu children in Palembang, 2) analyze the influence of the Arabic language on parents in naming Melayu children, and 3) analyze the naming transformation of Melayu children. The methodology used by researchers was a qualitative method using a socio-onomastic approach. The population was taken from students of STIKES Siti Khadijah Palembang and students of MTs.N 2 Palembang. Data were analyzed using Strauss and Corbin’s grounded theory model. The results showed: 1) there were three trends in naming Melayu children: a) hereditary (using bebangso); b) Arabic language; and c) modern trends. 2) Arabic language influences parents in naming children in various ways: a) on community construction; b) resistance; and c) the influence of public figures. 3) the transformations of the naming of Melayu children in Palembang were: a) naming transformation of children from the descent, Arabic language, and modern to westernized; b) shift in the referential system; and c) the cause of this transformation is a modernization factor that caused parents to transform in naming their children from Arabic language names transformed into modern names. Currently, naming children using Arabic language names is less represented rather than in the early 2000s. This transformation gives birth to a global society, not a local community, which is marked by the names of modern and westernized children.